'You are in Taiwan, Speak Chinese': Identity, language ideology, and sociolinguistic scales in online interaction. (December 2019) - Lee, Wan-Hsin; Su, Hsi-Yao
Highlights: An identity debate on a Taiwanese-American's use of English in Taiwan is examined. Online metapragmatic comments reveal conflicting language ideologies. Social media facilitate other-constructed identity work. "Foreigner, " "Taiwanese-American, " and "ABC" are redefined in online discussion. Identity, ideology and indexicality link linguistic performance to social context. Abstract: This study investigates how local identities of Taiwan are discursively constructed and how language ideologies concerning Chinese and English are manifested in the process in online discussion. We examine dynamics of identity work by drawing from metapragmatic discourse on social media regarding a verbal confrontation in Taiwan. A local Taiwanese driver with limited English competence was verbally attacked in English by an American-born-Taiwanese passenger. This passenger's nationality, ethnicity, and controversial linguistic performance lead to heated identity debates online. We look into the role language plays in these online debates and explore how social media serve as an important site for ideological contestation and identity construction. Specifically, we discuss (1) how viewers discursively construct this American-born-Taiwanese as an outgroup member through pronouns and identity labels, such as Taiwanese and ABC, (2) how his (presumed) competence in English or Chinese plays a critical role in deauthenticating him either as a 'real' Taiwanese or as a 'real' American, and (3) how various language ideologies are manifested through the aforementioned process of identity construction.